Pemanfaatan Olahan Kedelai Dalam Proses Pembuatan Tempe Untuk Meningkatkan Pendapatan Masyarakat - Tri Mutia Puspitasari; Suryati Suryati; Sumaina Duku (Social Science and Contemporary Issues Journal, 2023)
This research discusses "Using Processed Soybeans in the Tempe Making Process to Increase Community Income". This research aims to find out about the use of processed soybeans in the process of making tempeh and tempeh marketing strategies to increase people's income in Lorong Asia, Plaju Ulu Village, Plaju District. This research uses descriptive qualitative research, the data collection tools used are interviews, observation, and documentation. The subjects of this research were Tempe craftsmen at the Plaju Ulu Tempe Crafts Center. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion. The results of this research are that the process of making tempeh takes 96 hours or around 4 days with several stages, namely the first stage of washing soybeans, the second stage of boiling, the third stage of soaking, the fourth stage of washing again, the fifth stage of fermentation, the sixth stage of molding. 2. The marketing strategy used by the craftsmen at the Plaju Ulu Tempe crafting center is still simple, selling tempeh directly to traditional markets around Plaju. Such as the Main Market, Mariana Market, and Tegal Binangun Market, and also collaborates with retailers and restaurants. Always pay attention to the quality and quality of the products they produce so that consumers remain loyal to buy the tempeh they produce and their income can meet their daily living needs, including food, clothing, housing, and education, thereby achieving prosperity